Advanced characteristics of cement-treated materials with respect to strength performance and damage evolution - Korakod Nusit (2018)
© 2016 American Society of Civil Engineers. Cement-stabilized base (CSB), a cement-stabilized material for road pavement construction activities, generally has better essential properties than an unbound granular material, a commonly used material for the pavement base structure. However, CSB requires further investigation to improve understanding of its performance and maximize its effective use. This study aims to characterize CSB with respect to its strength performance and damage evolution under static and dynamic loading conditions. Furthermore, a new mix-design concept for CSB, based on more rational mix-design parameters and processes, was developed. The standard crushed rock from a local pit in Western Australia was used as the parent material of CSB test specimens with varying cement contents in the study. The CSB characteristics under monotonic and dynamic compressive loading conditions were also examined. The tests were established to investigate the influences of loading rates to material responses and damage evolutions. The findings show that the strength of CSB depends on the moisture content at compaction, dry density, and compaction degree. According to the study results, a cement content ranging between 3 and 7% was suggested to obtain an effective CSB. The strength of CSB could also be estimated from a range of water-cement ratios and curing durations. However, this is valid only for CSB prepared from the moisture content at optimum moisture content (OMC) and greater. Under compression tests of dynamic loading and static loading, test results reveal that the responses of CSB test specimens under different rates of loading are explicitly different. The damage evolution through the damage parameter can be successfully used to capture behavior differences of CSB under various loading regimes of static and dynamic. Finally, concern about using design parameters derived from the static loading tests could arise due to the difference in the intrinsic behavior of CSB under static and dynamic loading conditions, based on the test results in this study.